Upaya Indonesia Melalui Program Indonesia Spice Up The World dalam Mengenalkan Rempah dan Kuliner di Mancanegara - Septia Deva Ristiyanti; Havidz Ageng Prakoso (Madani: Jurnal Politik dan Sosial Kemasyarakatan, 2022)
The Government’s program, namely Indonesia Spice Up The World is one of the Indonesia government’s effort to improve Indoneia culinary and spices which has been planned since June 2020 with an implementation target starting in 2021-2024. With the aim introducing Indonesian spices and culinary delights to the world community as an effort to increase local spice exports and increase the diaspora of Indonesia restaurants. This study aims to analyze and provide information related to the importance of the Goverment’s program, namely Indonesia Spice Up The World which is expected to be a forum for introducing spice products and expanding Indonesia restaurants. This study used a qualitative mrthod with descriptive analysis research type by processing data that originates from library research. The approach in this study uses nation branding by looking at Indonesia Spice Up The World as a program to support the Indonesia Government efforts. The research result obtained are in line with the four pillars in the Indonesia Spice Up The World program whose development does not solely use culinary delights, but is suppoerted by spicesm Indonesia restaurant, processes spice products and culinary destinations. The Indonesia government then became a competition for more coorperation with importers of spices, boosting the local culinary industry and boosting local and global sectors so that Indonesia’s condiments would be able to consistenly attend international markets.